Leafminer Parasitoid Opius dissitus Muesebeck (Insecta: Hymenoptera: Braconidae) - Jian Li; Dakshina Seal; Gary Leibee (EDIS)
Leafminers are usually the larvae of insects that feed or mine inside plant leaves, and Opius dissitus is a wasp endoparasite that keeps the population of Liriomyza leafminers in check. This 2-page fact sheet was written by Jian Li, Dakshina Seal, and Gary Leibee, and published by the UF Department of Entomology and Nematology, October 2011. Reviewed December 2014.